PENERAPAN LEAN MANUFACTURING MENGGUNAKAN WASTE ASSESSMENT MODEL PADA PROSES PRODUKSI DI WORKSHOP KIDS PLAYGROUND PT XYZ - Alfathsyah, Arrasyid; Tri Purwandari, Aprilia; Nurhasanah, Nunung; Aribowo, Budi (LPPM Universitas Bina Bangsa, 2024)
Manufacturing companies today must be able to compete with each other, one way is to improve operational performance. Lean manufacturing plays an important role in minimizing waste and increasing productivity. PT XYZ Workshop is a provider of children's amusement parks, facing challenges in production capacity, especially for large projects. PT XYZ Workshop experienced various problems, including storage, production planning, material handling, and quality control during 2022-2023. This study applies lean manufacturing to identify and overcome production problems in PT XYZ workshop. The methods used include Waste Assessment Model (WAM) and Pareto Diagram to analyze critical waste, 5 Why Analysis to identify root causes, and FMEA to determine Potential Failure Cause with the highest RPN value. The results show that critical waste consists of Defect (19.46%), Over Production (18.72%), Inventory (17.44%), Motion (13.89%), and Waiting (10.72%). The main root causes are